EVALUATION OF THE EFFICACY OF THE INSECTICIDES CLOSER AND SIVANTO PRIME AND THE COMPOUND POTASSIUM SILICATE IN CONTROLLING THE CABBAGE APHID (BRASSICA OLERACEA VAR. CAPITATA L.) (HEMIPTERA: APHIDIDAE) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
A field experiment was carried out in Al-Alam District, Salahuddin Province, Iraq, following a randomized complete block design (RCBD). The study evaluated the efficacy of different aphid control strategies using Sivanto Prime, Closer, and potassium silicate, applied as single and combined treatments. Results indicated that the initial mean population density of nymphs and adults was 32.4 individuals per plant before treatment. However, a significant reduction was observed after application, with Sivanto Prime and Closer recording 1.1 and 1.3 individuals per plant, respectively, two weeks post-spraying. Remarkably, dual treatments such as Closer + potassium silicate and Sivanto Prime + Closer resulted in the lowest aphid populations, reaching 1.36 and 1.48 individuals per plant, respectively. In contrast, the Sivanto Prime + potassium silicate mixture did not achieve the expected suppression, as populations remained comparatively higher. Statistical analysis confirmed significant differences among treatments at the 0.05 probability level, with an LSD value of 0.5224. Overall, the findings highlight that pesticide combinations, particularly those involving Closer, could serve as an effective strategy for managing aphid infestations under field conditions.